2021
DOI: 10.3390/children8060521
|View full text |Cite
|
Sign up to set email alerts
|

The Child Behavior Checklist as a Screening Instrument for PTSD in Refugee Children

Abstract: Thousands of refugees who have entered Europe experienced threatening conditions, potentially leading to post traumatic stress disorder (PTSD), which has to be detected and treated early to avoid chronic manifestation, especially in children. We aimed to evaluate and test suitable screening tools to detect PTSD in children. Syrian refugee children aged 4–14 years were examined using the PTSD-semi-structured interview, the Kinder-DIPS, and the Child Behavior Checklist (CBCL). The latter was evaluated as a poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…Eleven studies were identified that investigated mental health screening approaches specific to refugee children and adolescents [ 52 , 57 , 58 , 59 , 61 , 62 , 67 , 82 , 89 , 97 , 100 ]. Children and adolescents between the ages of 6 months to 18 years old were included and all identified screening programs were completed post-arrival to the resettlement country.…”
Section: Mental Health Screening Approaches For Refugee Children and ...mentioning
confidence: 99%
See 4 more Smart Citations
“…Eleven studies were identified that investigated mental health screening approaches specific to refugee children and adolescents [ 52 , 57 , 58 , 59 , 61 , 62 , 67 , 82 , 89 , 97 , 100 ]. Children and adolescents between the ages of 6 months to 18 years old were included and all identified screening programs were completed post-arrival to the resettlement country.…”
Section: Mental Health Screening Approaches For Refugee Children and ...mentioning
confidence: 99%
“…Children and adolescents between the ages of 6 months to 18 years old were included and all identified screening programs were completed post-arrival to the resettlement country. All studies included adolescent populations (ages 10–18) and fewer studies included children below the age of 10 [ 58 , 59 , 82 , 89 , 100 ]. The programs reported that there is variability in the timing of presentations of mental health disorders; thus, an early assessment of the psychological needs of children and families allows for timely targeted support [ 58 , 59 ].…”
Section: Mental Health Screening Approaches For Refugee Children and ...mentioning
confidence: 99%
See 3 more Smart Citations